Effect of large-scale anisotropy on the small-scale structure of turbulence - Morshed, Khandakar Niaz, author; Dasi, Lakshmi Prasad, advisor; Kirkpatrick, Allan, committee member; Gao, Xinfeng, committee member; Venayagamoorthy, Subhas Karan, committee member (Colorado State University. Libraries, 2014)
Even though the small-scale structure of turbulence has been hypothesized to be locally isotropic with universal properties, numerous studies document the departure from local isotropy and universality in the presence of strong mean shear (or large-scale anisotropy). The goal of this work is to elucidate the effects of strong shear on the small-scale structure with emphasis on the physical mechanism through which mean shear deviates local structure from isotropy. Two dimensional time-resolved particle image velocimetry (PIV) experiments were performed in a stationary turbulent flow past a backward facing step at Reynolds numbers 13600 and 5500 based on the maximum velocity and step height. Large-scale anisotropic properties of the flow along with local turbulence characteristics were quantified in detail. Special points of interest distributed within the measurement domain for varying large-scale anisotropic characteristics were probed to analyze small-scale structure. Results show that velocity structure functions and their scaling exponents systematically align with the principal directions of deformation of the mean flow field. Furthermore, the probability density function (PDF) of the instantaneous dissipative scales indicate a potentially universal mechanism of how mean shear affects the distribution of dissipative scales captured through a local Reynolds number based on mean shear and dissipation rate. PDFs of the instantaneous dissipative scales in all directions demonstrate that mean shear strength and local principal axis directions dictate the behavior of structure functions, correlation functions, thereby influencing the dissipative scale PDFs in a directionally dependent manner.
Keywords: structure function; small-scale; turbulence; anisotropy; shear flows